Analysis of Pre-service Science Teachers' Technological Pedagogical Content Knowledge (TPACK) - Khasanah, A. N.; Septiyanto, A.; Jumadi, J.; Wilujeng, I.; Hidayah, E. N. (Journal of Science Education Research, 2025)
Professional teachers are expected to be able to integrate TPACK into their learning to meet the demands of changing science and technology in the world of education. This study examined the TPACK used by pre-service science teachers, as evidenced by the direct application of preschool field introductions in Indonesia called PLP. The study was a mixed method study using an Explanatory Sequential Design approach. The quantitative data collection instrument employed a survey method for pre-service science teachers participating in PLP. Technical triangulation was used in qualitative data collection instruments, such as observations, interviews, and documents. Data analysis Techniques used descriptive quantitative and qualitative data. The quantitative results showed that the TCK (3.50) and TK (3.43) domains were in the high category, followed by CK (3.24), PK (3.21), TPK (3.17), PCK (3.15), dan TPACK (3.10) in the moderate category. Qualitative evidence suggests that pre-service science teachers used the seven TPACK domains in their learning during PLP, as evidenced by observation, interviews, and documentation. The research has implications for studying longitudinal conducting to track the development of TPACK competencies over time, providing insights into how these skills evolve from training through to professional teaching.